Monitoring in non-traumatic coma. Part I: Invasive intracranial measurements. Issue 8 (August 1988) - Tasker, R C; Matthew, D J; Helms, P; Dinwiddie, R; Boyd, S
Abstract : The arterial blood pressure, intracranial pressure, and organ system failure scores were reviewed for 49 infants and children with non-traumatic coma from various causes. The neurological outcome was good in 21 patients, moderate in five, and poor in 23. There was no significant difference in maximum intracranial pressures between patients with a good outcome and those with a poor one, but patients with a poor outcome had significantly lower minimum cerebral perfusion pressures. During the period of admission 18 patients had cardiovascular failure, none had renal failure, and two developed severe coagulopathy. Seventeen of the 19 patients in whom at least one of these systems failed died. Our findings emphasise the diversity of illnesses associated with raised intracranial pressure in children and the number who develop multiple organ failure, and the values and limitations of using minimum cerebral perfusion pressure and the organ system failure scores as guides to severity of illness and prognosis.